2015
DOI: 10.4049/jimmunol.1402124
|View full text |Cite
|
Sign up to set email alerts
|

KIR and HLA Genotypes Predictive of Low-Affinity Interactions Are Associated with Lower Relapse in Autologous Hematopoietic Cell Transplantation for Acute Myeloid Leukemia

Abstract: Killer cell Ig–like receptors (KIRs) bind cognate HLA class I ligands with distinct affinities, affecting NK cell licensing and inhibition. We hypothesized that differences in KIR and HLA class I genotypes predictive of varying degrees of receptor–ligand binding affinities influence clinical outcomes in autologous hematopoietic cell transplantation (AHCT) for acute myeloid leukemia (AML). Using genomic DNA from a homogeneous cohort of 125 AML patients treated with AHCT, we performed KIR and HLA class I genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 81 publications
1
30
0
Order By: Relevance
“…35, 114, 115 Recognition of Bw4 by KIR3DL1 is sensitive to polymorphism both within and outside the Bw4 motif, as well as to the sequence of the bound peptide 42, 63, 116, 117, 118. Early work showed that HLA‐Bw4 allotypes with I80 formed more potent ligands for KIR3DL1 than those with T80,119 a functional difference reinforced by associations with disease outcome 27, 58, 120, 121, 122. However, recent high‐resolution studies have identified several I80 Bw4 allotypes that are poorly recognized by KIR3DL1, providing weaker KIR3DL1 ligands than selected T80 Bw4 allotypes 39, 41, 123.…”
Section: Kir Ligand Bindingmentioning
confidence: 99%
“…35, 114, 115 Recognition of Bw4 by KIR3DL1 is sensitive to polymorphism both within and outside the Bw4 motif, as well as to the sequence of the bound peptide 42, 63, 116, 117, 118. Early work showed that HLA‐Bw4 allotypes with I80 formed more potent ligands for KIR3DL1 than those with T80,119 a functional difference reinforced by associations with disease outcome 27, 58, 120, 121, 122. However, recent high‐resolution studies have identified several I80 Bw4 allotypes that are poorly recognized by KIR3DL1, providing weaker KIR3DL1 ligands than selected T80 Bw4 allotypes 39, 41, 123.…”
Section: Kir Ligand Bindingmentioning
confidence: 99%
“…Recipient HLA-C and HLA-B alleles were identified by high-resolution DNA-based HLA typing and were segregated, as appropriate, into the epitope groups HLA-C group 1 (HLA-C Asn80 : HLA-Cw1, 3, 7, 8, 13 and 14 alleles), HLA-C group 2 (HLA-C Lys80 : HLA-Cw2, 4, 5, 6, 12, 15, 17 and 18 alleles) and HLA-Bw4. HLA-Bw4 alleles were divided based on the presence of an isoleucine at position 80 (predicted high-affinity KIR3DL1 ligand) or a threonine at position 80 (predicted low-affinity ligand) (Marra et al, 2015).…”
Section: Hla and Kir Genotypingmentioning
confidence: 99%
“…HLA-Bw4 alleles were divided based on the presence of an isoleucine at position 80 (predicted high-affinity KIR3DL1 ligand) or a threonine at position 80 (predicted low-affinity ligand)(Marra et al, 2015). Recipient-Donor KIR Ligand Matching Prevents CMV Reactivation ª 2017 John Wiley & Sons Ltdas appropriate, into the epitope groups HLA-C group 1 (HLA-C Asn80 : HLA-Cw1, 3, 7, 8, 13 and 14 alleles), HLA-C group 2 (HLA-C Lys80 : HLA-Cw2, 4, 5, 6, 12, 15, 17 and 18 alleles) and HLA-Bw4.…”
mentioning
confidence: 99%
“…Thus, HLA‐KIR mismatch exists in everyone and some of our lymphocytes do not have KIR that recognizes our own HLA system. Prognostic role of such mismatches in an autologous setting have recently been highlighted in acute myeloid leukemia …”
Section: Discussionmentioning
confidence: 99%
“…Prognostic role of such mismatches in an autologous setting have recently been highlighted in acute myeloid leukemia. 24 Marin et al showed in 2012 that KIR2DS1 was the only independent factor for lower probability of achieving complete cytogenetic response, lower progression-free survival and overall survival in CML. 15 Recently, Yeung et al found that KIR2DL5B was associated with a lower event-free F I G U R E 1 Outcomes in CML patients according to KIR genotype.…”
Section: Discussionmentioning
confidence: 99%